Graduate of Riga Polytechnic Institute, Engineer and Athlete Mārtiņš Stabiņš - Lanka, Ērika (History of Engineering Sciences and Institutions of Higher Education, 2020)
The aim of the article is to reveal the performance of Mārtiņš Stabiņš, a graduate of the Faculty of Automation and Computer Technology (1972; FACT) of Riga Polytechnic Institute (RPI), in the profession of engineer and high achievements in sports, becoming a Latvian champion in athletics several times, to reveal his daily life during his study years in the 1960s–1970s. Despite the fact that M. Stabiņš' sports achievements have already described, this article summarizes his successes as well as reveals hitherto little-known and unpublished documents about his family, daily life, developments and interests. This is the first major research on the life of an engineer and athlete during seven decades. The resources used in the research are the personal archives of M. Stabiņš and of the author, documents of the National Archives of Latvia, and the collection of the National Library of Latvia.